DESIGN OF THE CONSTRUCTION MANAGEMENT ASPECT OF THE KARAWANG TOLL ACCESS (INTERCHANGE) PROJECT - Fikri Akbar, Alfredo
Karawang Regency is one of the industrial cities with high transportation demands in West Java. In Karawang Regency city planning to accommodate these demands, a road will be built to connect the Jakarta Cikampek Toll Road, Suryacipta Industrial Estate, and the South Jakarta Cikampek II Toll Road. Therefore, planning and designing access roads (interchange) connecting the South Jakarta Cikampek II Toll Road with the connecting road, are required. The designed access road consists of 4 ramps, with a total span length of 6839.16 m, and a total road area of 38,744.732 m2. The road construction type mainly consists of subgrades, with 2 bridge spans which will cross a river and the South Jakarta Cikampek II Toll Road. The design of both bridges implements the usage of prestressed girders with simple supports on abutments. In addition, the foundations of the bridge structures are designed with bored piles. The planning and design of the Karawang interchange reviews aspects of construction engineering management, which includes the composing of Work Breakdown Structures, site planning and construction methods, calculation of work volume and productivity, construction costs, and scheduling. The Work Breakdown Structures covers work zone plans and job requirements: preparatory works, earthworks, substructures, superstructures, road pavements, and road facilities. Subgrade construction methods include soil excavation and backfilling. Meanwhile, the construction of foundations and concrete structures implements the cast in situ method, except for the bridge girders which implement precast method and are installed using crawler cranes. Calculation of work quantity and productivity implements manual calculation method and lead resources method as well as enumeration in determining the unit price. Project scheduling are formulated using Microsoft Project Software, with the outputs of a Gantt Chart and Precedence Diagram. References for calculating construction costs include SNI, Jurnal Harga Satuan, and Peraturan Menteri PUPR No. 28 tahun 2016. The estimated cost of the project is Rp. 255,297,647,435.06 with a construction operational time of 259 working days (5 working days a week), or 12 months (1 year).